Characterization of physical parameters of the terminals of container of Spanish harbor system (2009)
The widespread use of management and exploitation ratios, taken from international literature that do not conform to the reality of the Spanish port system, makes it difficult to plan and manage the operation of Spanish container terminals. This is a consequence of the lack of characterization of the physical parameters of the container terminals necessary for exploitation. The container terminals of the Spanish port system are very heterogeneous and cannot be characterized from international operating ratios, so an own study is necessary to obtain generalities of the Spanish port container scenario. The contribution of this article, in the field of port exploitation, involves characterizing the container terminals of the Spanish port system from the values ​​that adopt the fundamental physical parameters (draft, surface, number of cranes, etc.) for the exploitation of a terminal, allowing to know the reality of the Spanish port system. This study allows us to characterize, at present, the main physical parameters of operation of container terminals by establishing some management and exploitation ratios that are characteristic of the reality of the port system in Spain that no previous study had presented to date. The research is carried out in the doctoral thesis. The objective of this is to obtain design parameters of container terminals from demand data, through a systemic study of the terminals and by grouping them according to these parameters, with a broader scope than the one developed in this article, in which only a part of the thesis is presented and whose objective is to represent the values ​​adopted by the physical operating parameters in the container terminals of the Spanish port system and the relations that occur between them, these Values ​​are necessary when addressing the planning of a terminal. The study carried out has allowed us to conclude that Spanish container terminals are very heterogeneous, the maritime scenario is characterized by small, medium and / or large terminals moving volumes of traffic not very high, whose docking line is not equipped with clearance and the Available surface is somewhat limiting. Future research should focus on improving the limitations presented in Spanish container terminals, pointing out why these specificities occur and how they condition the operation of the terminals both positively and negatively.